Analisis Sentimen Komentar Youtube Terhadap Food Vlogger Dengan Menggunakan Metode Naïve Bayes - Harahap, Sulistia Maharani; Kurniawan, Rakhamat (LPPM UNIKA Santo Thomas Medan, 2024)
YouTube is currently the media most frequently accessed by internet users in Indonesia with a percentage of 88%, then WhatsApp at 83%, Facebook at 81%, and Instagram at 80%. One of the themes that is often uploaded is about food reviews and people who upload them are called food vloggers. Food vloggers influence millennial audiences, namely before and after food consumption. The purpose of food review videos is to provide reviews of food in terms of taste, price, quality, atmosphere, etc. Other people also have the freedom to comment on food review videos. This research aims to analyze public sentiment towards food vloggers using data from YouTube social media. This research aims to analyze sentiment using the Naïve Bayes algorithm method for food vloggers used to analyze sentiment with an accuracy value of 44.8276%, precision of 16% or 0.16%, recall of 100% or 1.00%, and f1-score of 27% or 0.27%. This sentiment analysis can be a reference in understanding food vlogger preferences.